The Strengthening of Peace Organization by Buddhist Integrations - et. al., Phrakruwiboonjetiyanuruk, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fostering a peaceful organization in the workplace requires the collaboration of its members join together in one direction for any organization to move forward that requires the cooperation of its members. The purpose of this article was to propose a way to live together happily by integrating Buddhist principles. Ten objectivity principle was used for speech that should be spoken, which before the speaker says anything should be considered. Ponder the impact of the message on whether it will affect the situation in a positive or negative direction. It is also necessary to consider the context of the audience and adjust the idioms, expressions, and attitude while talking to focus on the success of communication in a positive direction. This article will present the issue of managing conflicts, managing happiness, by integrating 10 objects in the administration of happiness organizations, hoping that when applying principles. The members of the organization will be happy to work continuously.